ANALYSIS OF POSTOPERATIVE PAIN AFTER EXTRACTION OF IMPACTED MANDIBULAR THIRD MOLARS AND ADMINISTRATION OF PREEMPTIVE ANALGESIA - Deyan Neychev; Ivan Chenchev; Kiril Simitchiev (Peytchinski Publishing, 2017)
patients because of the effect of pain symptoms on the healing process and quality of life. The objective of this study is to make a quantitative and qualitative assessment of the postoperative pain in patients to whom preemptive analgesia was administered. Material and Methods: This is a randomised, placebo-controlled study in 80 patients who underwent surgical removal of impacted mandibular third molars. The patients were divided into three groups - with the preemptive administration of placebo, metamizole sodium and nimesulide. The short form of the McGill Pain Questionnaire (SF-MPQ) and the Visual Analogue Scale (VAS) were used for assessment and analysis of postoperative pain. Results: For the first 24 hours after molar extraction the comparison of the values of the various pain components showed a superior effect of the preemptive analgesia with nimesulide for the alleviation of sensory and total pain compared to metamizole sodium and placebo. In all three groups, pain intensity was highest at postoperative hour 6. Conclusion: Preemptive use of NSAIDs in the extraction of impacted mandibular third molars reduces the perception of postoperative pain and its intensity.